Pengembangan GameFunny English Menggunakan Unity3d - Ardiman Firmanda; Riwinoto Riwinoto (Politeknik Negeri Batam, 2014)
In Indonesia Learning English still very difficult and sometimes make scary for some student. they have difficult to learning English, especially in writing and memorizing vocabulary. In reality, author develop interactive learninggame that isgame funny english. This game develop by unity3d 4.3.4 as game engine and maya3d as object modeling. The selection games asenglishlearning is right because the game can giveusers a scenario for developed a real-life experience.